Effect of Perceived Usefulness And Perceived Ease of Use On The Acceptance of Internal Audit Technology - Siryasti Siryasti; Nispa Sari; Indah Pratiwi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This research aims to examine the influence of perceived usefulness and perceived ease of use on the acceptance of internal audit technology among university internal auditors in Palopo City, emphasizing the importance of digital tool adoption for improving audit quality and institutional accountability. Methodology: A quantitative approach was employed, utilizing primary data collected through questionnaires distributed to auditors who actively use audit applications or software. Data analysis focused on measuring the impact of the two perceptual variables on technology acceptance. Results: The findings indicate that both perceived usefulness and perceived ease of use have a positive and significant effect on auditors' acceptance of internal audit technology. Findings: Auditors are more inclined to adopt such tools when they recognize clear functional benefits and when the system is user-friendly. Novelty & Originality: This study offers novelty by focusing specifically on technology acceptance among university internal auditors—a professional group seldom examined in prior research. Its originality lies in the integrated assessment of benefit perception and user-friendliness as joint determinants of adoption behavior in the academic audit environment. Conclusions: The study underscores the necessity for universities to optimize system features, simplify interfaces, and enhance training programs to foster greater technology adoption and improve audit effectiveness. Type of Paper: This paper is an empirical research paper.